Improved Control of Grid-connected DFIG-based Wind Turbine using Proportional-Resonant Regulators during Unbalanced Grid - Yassir El Karkri; Alexis B. Rey-Boué; Hassan El Moussaoui; Johannes Stöckl; Thomas I. Strasser (Energies, 2019)
The quality of power and current control are the greatest challenges of grid-connected wind farms during abnormal conditions. The negative- and positive-sequence components of the grid currents may be injected into a wind generation system during grid faults, which can affect the power stability and damage the wind system. The proposed work assures a low-voltage ride through capability of doubly-fed induction generator- based wind turbines under the grid voltage sag. A new technique to protect the wind system and to recompense the reactive power during failures of the utility grid according to the Spanish grid code is proposed. The control design is implemented to the power converters, and the grid current regulation is developed by using proportional-resonant regulators in a stationary two-phase (αβ) reference frame. The control performance is significantly validated by applying the real-time simulation for the rotor-side converter and the hardware in the loop simulation technique for the experiment of the generator’s grid-side converter control.